2021
DOI: 10.1088/1361-6641/abe6da
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of device characteristics of plasma-treated indium gallium zinc oxide thin-film transistors through thermal annealing

Abstract: In this study, an Ar/O2 plasma mixture treatment with different proportions of O2 was used to reduce the oxygen vacancy density in an amorphous indium gallium zinc oxide (a-IGZO) thin film. The objective was to enhance the field-effect carrier mobility in a thin-film transistor (TFT) with the IGZO film as the channel layer. Atomic force microscopy revealed that the roughness of the IGZO film after plasma treatment was higher than that of the untreated film; however, the surface roughness of the IGZO film decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…Moreover, rapid annealing avoids the problem of the film surface being overoxidized, due to the short ramp-up and ramp-down times. Furthermore, the thermally activated atom diffusion caused by the rapid annealing process can reduce the surface roughness and repair the damage of the UV treatment on the film surface . In summary, UV-ORTA treatment enhances the film quality by suppressing structural defects and O-deficiency defects and enables the low-temperature preparation of high-performance α-IGZO TFTs based on HfAlO high- k gate dielectrics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, rapid annealing avoids the problem of the film surface being overoxidized, due to the short ramp-up and ramp-down times. Furthermore, the thermally activated atom diffusion caused by the rapid annealing process can reduce the surface roughness and repair the damage of the UV treatment on the film surface . In summary, UV-ORTA treatment enhances the film quality by suppressing structural defects and O-deficiency defects and enables the low-temperature preparation of high-performance α-IGZO TFTs based on HfAlO high- k gate dielectrics.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the trapped electrons at the interface will weaken the induction effect of the gate voltage on the electrons, resulting in a positive shift of the transfer curve. Some studies show that the negative shift of threshold voltage in the NBS test is caused by the release of electrons from the absorbed water molecules on the surface of the α-IGZO film . Moreover, the ionization of shallow-level donors and the release of trapped electrons from trap defects in the channel layer under negative gate voltage lead to an increase of electron concentration in the channel layer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because oxygen vacancies are important for electron donation in the a-IGZO channel layer, the decreased OII peak intensity shown in the XPS analyses corresponded well with the reduced carrier concentration, which could be ascribed to a higher resistivity as a result of the increased O2 plasma time, as shown in Table 2. Therefore, as the O2 plasma time increased, the reduced carrier concentration in the IGZO channel layer may have resulted in an increase in the threshold voltage (Vth) of the IGZO TFT devices [13,17,24]. For the analysis of the SIMS depth profile results, we fabricated test samples with a 50 nm thick Mo/100 nm thick TEOS oxide/40 nm thick a-IGZO structure on silicon sub- For the analysis of the SIMS depth profile results, we fabricated test samples with a 50 nm thick Mo/100 nm thick TEOS oxide/40 nm thick a-IGZO structure on silicon substrates that were the same as the structure of the top-gate IGZO TFT devices.…”
Section: Electrical Characteristics Of Igzo Tfts At Various O 2 Plasm...mentioning
confidence: 99%
“…The results indicated that O 2 and N 2 plasmas decreased oxygen vacancies, but Ar plasma treatment increased them. Liu et al recently reported [17] on IGZO thin films that were treated with an Ar/O 2 plasma combination with various oxygen content ratios, resulting in the bottom-gate IGZO TFTs have improved device operation characteristics. Wang et al reported [18] the O 2 plasma treatment on gate dielectrics (Al 2 O x ) for a-IGZO TFTs and demonstrated that O 2 plasma treatment can improve the gate dielectric performance.…”
Section: Introductionmentioning
confidence: 99%